2002
DOI: 10.4319/lo.2002.47.4.0934
|View full text |Cite
|
Sign up to set email alerts
|

Prey resource use by coexistent hydromedusae from Friday Harbor, Washington

Abstract: Prey selection patterns were quantified for a sympatric group of hydromedusae from Friday Harbor, WA. Selection patterns varied between species, but were largely replicable between sample dates and resembled dietary patterns found in similar studies from neighboring regions. Ambush-foraging medusae (Aglantha digitale, Sarsia tubulosa, and Proboscidactyla flavicirrata) fed primarily on crustacean and ciliated prey but the dietary niches of these hydromedusan species centered on different fractions of the availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
55
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 26 publications
5
55
0
2
Order By: Relevance
“…In situ prey-selection data indicate that the different mechanisms of prey capture used by rowers versus jetters result in dietary differences and, therefore, different trophic roles (Costello & Colin 2002). We would predict, based upon the morphology, swimming performance and prey selection of the different medusan groups, that in order to optimize foraging success and trophic impact, rowing medusae should maximize and jetting medusae should minimize their time spent swimming.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
See 3 more Smart Citations
“…In situ prey-selection data indicate that the different mechanisms of prey capture used by rowers versus jetters result in dietary differences and, therefore, different trophic roles (Costello & Colin 2002). We would predict, based upon the morphology, swimming performance and prey selection of the different medusan groups, that in order to optimize foraging success and trophic impact, rowing medusae should maximize and jetting medusae should minimize their time spent swimming.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…Understanding determinates of the foraging behavior of hydromedusa can provide insight into factors determining their trophic impact. The modes of propulsion, bell morphology and prey selection vary among hydrozoan taxa and are thought to be directly linked to the foraging behavior of hydromedusae (Colin & Costello 2002, Costello & Colin 2002. Accordingly, Costello & Colin (1995) have suggested that propulsion and bell morphology can be used to predict the impact that different hydromedusae have upon zooplankton prey populations.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Predation by medusae plays an important role in the trophic ecology of many pelagic ecosystems (Purcell, 1989;Matsakis and Conover, 1991;Olesen, 1995;Costello and Colin, 2002). Despite its importance, many of the mechanisms that determine predation rates and prey selection are poorly defined.…”
Section: Introductionmentioning
confidence: 99%